2013
DOI: 10.1002/jhm.2077
|View full text |Cite
|
Sign up to set email alerts
|

Delirium superimposed on dementia is associated with prolonged length of stay and poor outcomes in hospitalized older adults

Abstract: Background Current literature does not identify the significance of underlying cognitive impairment and delirium on older adults during and 30 days following acute care hospitalization. Objective Describe the incidence, risk factors, and outcomes associated with incident delirium superimposed on dementia. Design 24-month prospective cohort study Setting community hospital Patients 139 older adults (>65 years) with dementia Methods This prospective study followed patients daily during hospitalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
142
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(172 citation statements)
references
References 41 publications
12
142
1
6
Order By: Relevance
“…Fick et al further identified that patients with delirium superimposed on dementia had a higher likelihood of delayed discharge from hospitals. (13) Among patients with dementia, caregiver support and burden (14) are important predictors of pLOS, just as poor nutritional status (15) is an important predictor for older adults. Expectedly, clinical factors, (16) such as the principal admitting diagnosis and burden of comorbidities, have been shown to be important.…”
Section: Introductionmentioning
confidence: 99%
“…Fick et al further identified that patients with delirium superimposed on dementia had a higher likelihood of delayed discharge from hospitals. (13) Among patients with dementia, caregiver support and burden (14) are important predictors of pLOS, just as poor nutritional status (15) is an important predictor for older adults. Expectedly, clinical factors, (16) such as the principal admitting diagnosis and burden of comorbidities, have been shown to be important.…”
Section: Introductionmentioning
confidence: 99%
“…Delirium, a clinical syndrome that is defined as inattention and acute cognitive dysfunction affects an estimated 14-56% of all hospitalized elderly patients [12][13][14][15][16][17][18]. At least 50% of geriatric patients hospitalized annually in the US develop complications secondary to delirium with a mortality rate between 25-33% [12,13].…”
Section: Anemia and Deliriummentioning
confidence: 99%
“…At least 50% of geriatric patients hospitalized annually in the US develop complications secondary to delirium with a mortality rate between 25-33% [12,13].…”
Section: Anemia and Deliriummentioning
confidence: 99%
See 1 more Smart Citation
“…Comparada com demência isolada, esta sobreposição está associada a custos mais elevados, declínio funcional mais acentuado e maior mortalidade 51,52 Program (HELP), um programa de prevenção de delirium e declínio funcional que já foi implementado em mais de 200 hospitais do mundo todo 20,80 . As estratégias voltadas para reorientar pacientes, promover atividades terapêuticas, reduzir uso e doses de medicações psicoativas, promover mobilização, garantir tempo de sono, e manter hidratação e nutrição, mostraram-se efetivas em seus objetivos, economizando, anualmente, até US$ 9 mil por paciente internado 81 .…”
Section: Sobreposição Com Demênciaunclassified